Lone Star Tick Amblyomma americanum (Linnaeus) (Acari: Ixodidae) - Christopher J. Holderman; Phillip Kaufman (EDIS, 2013)
This document provides an overview of the lone star tick, Amblyomma americanum, detailing its distribution, life cycle, and medical significance. It highlights the tick’s ability to transmit various pathogens, including those causing ehrlichiosis, rickettsiosis, tularemia, and theileriosis. The article also discusses the tick’s habitat preferences, host associations, and management practices to control its population. Emphasis is placed on the tick’s expanding range and its role in public health concerns.